2019
DOI: 10.1007/s00430-019-00652-3
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the understanding of trimeric autotransporter adhesins

Abstract: Adhesion is the initial step in the infection process of gram-negative bacteria. It is usually followed by the formation of biofilms that serve as a hub for further spread of the infection. Type V secretion systems engage in this process by binding to components of the extracellular matrix, which is the first step in the infection process. At the same time they provide protection from the immune system by either binding components of the innate immune system or by establishing a physical layer against aggresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…This concept has changed since other factors, such as chaperones and the BAM (β-barrel Assembly Machinery) system are required for secretion of these proteins. Furthermore, more recently, it was shown that another system, the TAM (Translocation and Assembly Module) complex, is also required for the correct translocation of autotransporters into the outer membrane [ 51 , 52 , 53 ]. It was proposed that this complex spanning the periplasmic space might solve the energy problem to translocate proteins through the outer membrane [ 52 ].…”
Section: Bacterial Adhesinsmentioning
confidence: 99%
See 2 more Smart Citations
“…This concept has changed since other factors, such as chaperones and the BAM (β-barrel Assembly Machinery) system are required for secretion of these proteins. Furthermore, more recently, it was shown that another system, the TAM (Translocation and Assembly Module) complex, is also required for the correct translocation of autotransporters into the outer membrane [ 51 , 52 , 53 ]. It was proposed that this complex spanning the periplasmic space might solve the energy problem to translocate proteins through the outer membrane [ 52 ].…”
Section: Bacterial Adhesinsmentioning
confidence: 99%
“…Furthermore, more recently, it was shown that another system, the TAM (Translocation and Assembly Module) complex, is also required for the correct translocation of autotransporters into the outer membrane [ 51 , 52 , 53 ]. It was proposed that this complex spanning the periplasmic space might solve the energy problem to translocate proteins through the outer membrane [ 52 ]. Therefore, the current model proposes that the TAM and BAM systems would act in a concerted manner [ 51 , 54 ].…”
Section: Bacterial Adhesinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trimeric autotransporter adhesins are a diverse, simple, and widespread type Vc secretion pathway ( Dautin and Bernstein, 2007 ; Bernstein, 2019 ; Kiessling et al, 2020 ). TAAs are modular homotrimers with various lengths and domain complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Trimeric autotransporter adhesins are a diverse, simple, and widespread type Vc secretion pathway (Dautin and Bernstein, 2007;Bernstein, 2019;Kiessling et al, 2020). TAAs are modular homotrimers with various lengths and domain complexity.…”
Section: Introductionmentioning
confidence: 99%